Eye Care and Surma Use in Pakistani Neonates - Anwar, Zahid; Anwar, Shahid; Akram, Mateen; Ahmad, Sajad; Pirzada, Saima; Kanwal, Andleeb (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To document the methods of eye care and surma use in neonates. Study Design: Prospective cross-sectional study Place and Duration of Study: Fatima Memorial Hospital, Lahore Mayo Hospital Lahore and Sir Ganga Ram Hospital Lahore from 1st July 2020 to 31st December 2020. Methodology: Two thousand two hundred and thirty seven females (mostly mothers and female attendants) during ward rounds and outpatient clinics. The socio-demographic data, frequency of different eye care practices and Surma use in neonates were recorded. Results: Most participants aged between 20 to 40 years (70%), were urban (75.5%), and housewives (54%). Only 15% were illiterate, remaining having at least some schooling or more. 90% were married, though 52% (unmarried + married and no kid+ first-time mothers) did not have personal experience of baby care. Medical personnel had guided females and families in 49%. Of the counselling by relatives (15.2%), grandmothers were a common influence. For first eye care after birth, 67% would use clean water, 19.9% did not know, and 5.5% would use unsafe methods like antimicrobial agents or rose water. A majority (65%) of participants intended to use Surma, usually once a day, the commonest reason being beautification of eyes and face. There was no correlation between eye care method, use of Surma, and socio-demographics. Conclusion: We should prioritize the educations of our medical personnel as well the whole families and community.